CLINICAL STUDIES OF CEFOXITIN IN THE FIELD OF OBSTETRICS AND GYNECOLOGY - SUGIZAKI, KENZO; Seo, FUMIHIRO; MIYAGAMI, JUNSHI; KUNII, KATSUAKI; CHO, NANKUN; UEHARA, KAZUHIRO; NAKAYAMA, TETSUYA; SAITO, HIROSHI (CHEMOTHERAPY, 1978)
Clinical studies were done on cefoxitin, a new cephamycin antibiotic, in the field of obstetrics and gynecology and the following results were obtained. The drug was absorbed rapidly and transferred well into umbilical cord blood and amniotic fluid. Cefotitin was administered intravenously at a daily dose of 4 g (2g b.i.d.) to 16 patients (2 with carbuncles and wound abscess, 12 with intrapelvic infections and 2 with urinary tract infections). The clinical response was good in 12 cases and failed in 4 cases with the efficacy rate being about 75%. No noteworthy side effects were noted with the drug.